In my hands : memories of a Holocaust rescuer - Opdyke, Irene Gut, 1921-; Armstrong, Jennifer, 1961- (New York : Knopf : Distributed by Random House, 1999)
Recounts the experiences of the author who, as a young Polish girl, hid and saved Jews during the Holocaust.
Keywords: Opdyke, Irene Gut, -- 1921- -- Juvenile literature; Opdyke, Irene Gut, -- 1921-; Righteous Gentiles in the Holocaust -- Poland -- Biography -- Juvenile literature; World War, 1939-1945 -- Jews -- Rescue -- Poland -- Juvenile literature; World War, 1939-1945 -- Personal narratives, Polish -- Juvenile literature; Holocaust, Jewish (1939-1945) -- Poland -- Juvenile literature; Righteous Gentiles in the Holocaust; World War, 1939-1945 -- Jews -- Rescue; World War, 1939-1945 -- Personal narratives, Polish; Holocaust, Jewish (1939-1945) -- Poland